Hybrid Nanocomposites of Tenoxicam: Layered Double Hydroxides (LDHs) vs. Hydroxyapatite (HAP) Inorganic Carriers - Lauretta Maggi; Valeria Friuli; Giovanna Bruni; Alessia Rinaldi; Marcella Bini (Molecules, 2023)
The search for effective systems to facilitate the release of poorly bioavailable drugs is a forefront topic for the pharmaceutical market. Materials constituted by inorganic matrices and drugs represent one of the latest research strategies in the development of new drug alternatives. Our aim was to obtain hybrid nanocomposites of Tenoxicam, an insoluble nonsteroidal anti-inflammatory drug, with both layered double hydroxides (LDHs) and hydroxyapatite (HAP). The physicochemical characterization on the base of X-ray powder diffraction, SEM/EDS, DSC and FT-IR measurements was useful to verify the possible hybrids formation. In both cases, the hybrids formed, but it seemed that the drug intercalation in LDH was low and, in fact, the hybrid was not effective in improving the pharmacokinetic properties of the drug alone. On the contrary, the HAP–Tenoxicam hybrid, compared to the drug alone and to a simple physical mixture, showed an excellent improvement in wettability and solubility and a very significant increase in the release rate in all the tested biorelevant fluids. It delivers the entire daily dose of 20 mg in about 10 min.